Is pregnancy associated plasma protein-A (PAPP-A) a marker for adverse perinatal outcomes in preterm isolated oligohydramnios cases? - Gulten Ozgen; Burcu Dincgez Cakmak; Betul Dundar; Fatma Nurgul Tasgoz; Feyza Bayram; Burak Karadag (Elsevier, 2018)
Objective: Isolated oligohydramnios is defined as an amniotic fluid index below five centimeter with no other coexisting condition. There are still controversies about the management and pregnancy outcomes. A marker predicting these is crucial. Low pregnancy associated plasma protein-A levels were reported to be related with adverse pregnancy outcomes. We aimed to determine the role of first trimester pregnancy associated plasma protein-A for poor outcomes in preterm isolated oligohydramnios cases. Material and Methods: Fifty-one patients with singleton pregnancies diagnosed as isolated oligohydramnios at 28/0-36/6 weeks of gestation and 110 gestational age matched healthy controls between January and December 2015 were included. Maternal age, gestational age at delivery, mode of delivery, indication for cesarean section, Apgar scores at first and fifth minutes, birth weight, neonatal intensive care unit admission and mortality were recorded. Pregnancy associated plasma protein-A levels were compared between groups and its role in adverse perinatal outcomes was evaluated. Results: Pregnancy associated plasma protein-A levels and pregnancy outcomes were similar in two groups (p > 0.050) except birth weight, gestational age at delivery and presence of fetal distress. Pregnancy associated plasma protein-A levels did not differ in terms of delivery mode, presence of fetal distress, first and fifth minutes Apgar scores and neonatal intensive care unit admission (p = 0.323,0.650,0.990,0.112,0.853). Also, it was not determined as a risk factor for cesarean section, presence of fetal distress, low Apgar scores and neonatal intensive care unit admission. Conclusion: Pregnancy associated plasma protein-A, a well-known prognostic factor for some of high risk pregnancy conditions, may not be used as a marker in preterm isolated oligohydramnios cases.